Bangladesh : Public Expenditure Review - World Bank; Asian Development Bank (Washington, DC, 2013)
This public expediture review analyzes the state of public expenditure in Bangladesh, particularly their adequacy and appropriateness relative to the Government's broad economic and social goals. It aims to contribute to the Government's overall growth and poverty reduction efforts by offering suggestions about the efficient use of public resources and fiscally sustainable improvements in public services. The findings and detailed recommendations of this report, summarized below, have been organized around six issues: 1) restoring fiscal sustainability; 2) reducing the role of state-owned enterprises and strengthening their governance framework; 3) strengthening Annual Development Program spending; 4) strengthening public expenditure managmement; 5) enhancing the pro-poor bias of public spending; and 6) expanding the involvement of the private sector and improving the role of government.